2016
DOI: 10.1128/jvi.00320-16
|View full text |Cite
|
Sign up to set email alerts
|

Repair of a Mutation Disrupting the Guinea Pig Cytomegalovirus Pentameric Complex Acquired during Fibroblast Passage Restores Pathogenesis in Immune-Suppressed Guinea Pigs and in the Context of Congenital Infection

Abstract: Guinea pig cytomegalovirus (GPCMV) provides a valuable model for congenital cytomegalovirus transmission. Salivary gland (SG)-passaged stocks of GPCMV are pathogenic, while tissue culture (TC) passage in fibroblasts results in attenuation. Nonpathogenic TC-derived virus N13R10 (cloned as a bacterial artificial chromosome [BAC]) has a 4-bp deletion that disruptsGP129, which encodes a subunit of the GPCMV pentameric complex (PC) believed to govern viral entry into select cell types, and GP130, an overlapping ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…Yamada et al [117] first described a region of the GPCMV genome which appeared to contain homologues of HCMV PC and, more recently, Auerbach et al [118] concluded that the guinea pig genes GP129, GP131 and GP 133 are the homologues of the HCMV genes UL128, UL130 and UL131, and that the relevant recombinant proteins are immunoreactive with convalescent sera from infected animals [119]. Thus, the protein products of GPCMV GP129, 131 and 133 locus were referred to as the GP PC, and the mutations acquired during passaging in fibroblasts attenuated virus pathogenicity [120], whereas repair resulted in congenital transmission, intrauterine growth restriction and elevated pup mortality. Thus, it was concluded that a vaccine aimed at preventing congenital infection should contain PC.…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…Yamada et al [117] first described a region of the GPCMV genome which appeared to contain homologues of HCMV PC and, more recently, Auerbach et al [118] concluded that the guinea pig genes GP129, GP131 and GP 133 are the homologues of the HCMV genes UL128, UL130 and UL131, and that the relevant recombinant proteins are immunoreactive with convalescent sera from infected animals [119]. Thus, the protein products of GPCMV GP129, 131 and 133 locus were referred to as the GP PC, and the mutations acquired during passaging in fibroblasts attenuated virus pathogenicity [120], whereas repair resulted in congenital transmission, intrauterine growth restriction and elevated pup mortality. Thus, it was concluded that a vaccine aimed at preventing congenital infection should contain PC.…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…The GPCMV PC, in particular the GP129, also plays a role in macrophage-mediated dissemination of virus in vivo [59], possibly mediated through a putative CC chemokine function [54]. The GPCMV PC is also required for pathogenesis in experimentally challenged, non-pregnant animals [60]. Future work will be required to more fully characterize whether vaccination against the GPCMV PC exerts a beneficial effect by eliciting virus-neutralizing activity, or perhaps instead by inducing antibody responses that target an immunomodulatory or chemokine-like activity, conferred by the GP129 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Two-step galactokinase (galK)-mediated recombineering in E. coli (Warming et al, 2005) was used to modify BAC clone N13R10r129, which contains the GPCMV strain 22122 genome (McVoy et al, 2016), to include an expression cassette for NanoLuc ® luciferase. Sequences for all oligonucleotides used are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%